Primary health care rendered from mobile units: Can computers help? - T. McDonald; R. D. Chapman; J. MacKenzie (AOSIS, 1994)
The object of survey was to assess which aspects of the nurses' work in mobile clinics could be computerised with a beneficial effect on the quality of work. This paper is an analysis of how much time the nursing staff spent on various tasks. The results show that nurses are satisfied with their work, even in the face of difficult working conditions and a high workload. It was also found that computer and communications technology can promote greater efficiency in activities that represent 35% of a nurse's time.